Synergistic Effects in N, O‐Comodified Carbon Nanotubes Boost Highly Selective Electrochemical Oxygen Reduction to H2O2. Issue 27 (28th July 2022) - Xu, Shuhui; Lu, Ruihu; Sun, Kai; Tang, Jialun; Cen, Yaping; Luo, Liang; Wang, Ziyun; Tian, Shubo; Sun, Xiaoming
Abstract: Electrochemical 2‐electron oxygen reduction reaction (ORR) is a promising route for renewable and on‐site H2 O2 production. Oxygen‐rich carbon nanotubes have been demonstrated their high selectivity (≈80%), yet tailoring the composition and structure of carbon nanotubes to further enhance the selectivity and widen working voltage range remains a challenge. Herein, combining formamide condensation coating and mild temperature calcination, a nitrogen and oxygen comodified carbon nanotubes (N, O‐CNTs) electrocatalyst is synthesized, which shows excellent selective (>95%) H2 O2 selectivity in a wide voltage range (from 0 to 0.65 V versus reversible hydrogen electrode). It is significantly superior to the corresponding selectivity values of CNTs (≈50% in 0–0.65 V vs RHE) and O‐CNTs (≈80% in 0.3–0.65 V vs RHE). Density functional theory calculations revealed that the C neighbouring to N is the active site. Introducing O‐related species can strengthen the adsorption of intermediates *OOH, while N‐doping can weaken the adsorption of in situ generated *O and optimize the *OOH adsorption energy, thus improving the 2‐electron pathway. With optimized N, O‐CNTs catalysts, a Janus electrode is designed by adjusting the asymmetric wettability to achieve H2 O2 productivity of 264.8 mol kgcat –1 h –1 . Abstract : Using the double‐heteroatom comodified strategy, this work design a N, O‐comodified carbon nanotubes (N, O‐CNTs) electrocatalyst. The O and N atoms can regulate the adsorption energy of *OOH and *O, and the selectivity for H2 O2 reaches more than 95%. Moreover, a Janus electrode is designed using the catalyst to achieve H2 O2 productivity of 264.8 mol kgcat −1 h −1 .